The Impact of GPC3 rs2267531 Polymorphism on Hepatocellular Carcinoma Susceptibility (Central Asian Journal of Medical Sciences, 2025)
Objectives: To evaluate the association between the GPC3 rs2267531 polymorphism and hepatocellular carcinoma (HCC) in individuals from Mongolia. Methods: This study included 270 participants, consisting of 110 males and 160 females, with a mean age of 61.0 years (±9.5). Serum samples were collected from all participants, who were categorized into three groups: 90 patients with hepatocellular carcinoma (HCC), 90 individuals in the risk group (RG), and 90 healthy controls. The collected samples were analyzed using allele-specific polymerase chain reaction (PCR). Results: No significant differences in genotype and allele frequencies were observed between the HCC group and the risk or control groups. However, the frequency of the GPC3 C allele was significantly higher in females in the HCC group. Additionally, the protective GG genotype of GPC3 was found to have a significantly lower frequency in females in the HCC group. In contrast, HCV-positive individuals exhibited a higher frequency of the GC genotype. Conclusion: The GPC3 C allele frequency is associated with HCC in females, while the heterozygote GC genotype is linked to HCV infection in both genders. These findings suggest that the GPC3 rs2267531 polymorphism may play a role in HCC susceptibility, particularly in relation to gender and HCV status.